Culture Diversity Impacts on Teams Performance and Innovation Role in Dubai Private Sector - Al Najjar, Latifa (2012)
Cultural diversity is having a significant impact on organizations at the current time. This research will discuss the impact of this diversity on the performance and innovation of teams within organizations. In addition, it will consider the role of management in enhancing innovation. The research will consider the effects of cultural diversity on teams as reported in previous studies. In addition, it will analyse the effects reported in relevant studies which have looked at the experiences of different countries where cultural diversity has been prevalent. The research was conducted in a private company in the United Arab Emirates (UAE) and a qualitative approach was used which was based on interviews conducted with six participants from three units, all of which were part of the IT department of the company. The findings from the case studies show that cultural diversity affects the performance of a team if the criteria by which team members are selected are not defined properly to fit the work positions. In addition, the team’s performance will be affected if there is no communication between the team members. Finally, there will be an impact on the team if there is no measurement of each team member’s performance. In addition, the effects of cultural diversity on innovation vary depending on the team’s education and work knowledge and the ability of the manager to enhance the exchange of information. Furthermore, the team will be affected by cultural diversity if there are no proper means of monitoring the innovation within the team. The last effect discussed is the role of the manager in enhancing innovation. The case studies show that most managers are unable to overcome the issues that act against innovation. Additionally, some managers do not have sufficient knowledge to create an innovation processes for their teams, and hence the effects vary from team to team. Finally, this study recommends some steps to ensure that the cultural diversity of a team has a positive effect, which in turn will assist the organization to gain the maximum benefit from it.